2009
DOI: 10.1103/physreve.80.061127
|View full text |Cite
|
Sign up to set email alerts
|

Universality classes of the absorbing state transition in a system with interacting static and diffusive populations

Abstract: In this work, we study the critical behavior of a one-dimensional model that mimics the propagation of an epidemic process mediated by a density of diffusive individuals which can infect a static population upon contact. We simulate the above model on linear chains to determine the critical density of the diffusive population, above which the system achieves a statistically stationary active state, as a function of two relevant parameters related to the average lifetimes of the diffusive and nondiffusive popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The influence of particle diffusion in the critical behavior of absorbing state phase transitions has been a subject of growing interest, since analytical and numerical studies showed that diffusion is an important mechanism that can influence the critical behavior [5][6][7][8][9][10][11][12][13][14]. In particular, strong deviations from the directed percolation universality class have been recently reported for models with coupled diffusive and non-diffusive fields [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of particle diffusion in the critical behavior of absorbing state phase transitions has been a subject of growing interest, since analytical and numerical studies showed that diffusion is an important mechanism that can influence the critical behavior [5][6][7][8][9][10][11][12][13][14]. In particular, strong deviations from the directed percolation universality class have been recently reported for models with coupled diffusive and non-diffusive fields [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, some progress was made (see, for example [2][3][4]). In order to model the spreading of a disease, we consider a metapopulation model [5] where we couple a population of random walkers to a network, called diffusive epidemic process (DEP) [6][7][8][9][10][11][12]. Unlike the common lattice epidemic models, where a sedentary individual is placed in a node, we consider a population of moving individuals that can hop along the network edges while they can be contaminated while dividing the same network node with an already contaminated individual.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we consider the DEP [6][7][8][9][10][11][12], coupled to BA networks. The DEP is a well-studied model where a non-sedentary population is divided into two compartments: susceptible individuals and infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the models with local updates given by a contact process, when transport is dominated by brownian diffusion, can have different critical exponents in lower dimensions. The Diffusive Epidemic Process (DEP) [17][18][19][20][21][22][23][24][25][26] is an example of a system that presents a new universality class, where exponents in lower dimensions deviate from the exponents of the contact process (CP). The CP obeys the directed percolation (DP) universality class, and DEP in lower dimensions defines new universality classes [25].…”
Section: Introductionmentioning
confidence: 99%